AKTIVITAS APOPTOSIS SEL HELA OLEH FRAKSI AKTIF MAHONI: STUDI FLOWCYTOMETRY - Komala Sari, Diah; Ayu Widayanti, Gusti; Arifah, Nur (Jurnal Kesehatan dan Pembangunan, 2025)
Cervical cancer is a leading cause of death among women, particularly in developing countries with limited access to conventional treatment (Sung, 2021). Modern cancer therapy strategies focus on inducing apoptosis, a programmed cell death process that suppresses tumor progression (Elmore, 2022). Medicinal plants such as Swietenia mahagoni, which contain flavonoids and limonoids with cytotoxic effects, are promising sources of pro-apoptotic agents (Abotaleb, 2018; Syame, 2022). This study aimed to evaluate the apoptotic activity of the ethyl acetate fraction of Swietenia mahagoni leaves against HeLa cervical cancer cells in vitro using flow cytometry (Shapiro, 2024). HeLa cells were treated at the IC?? concentration and stained with Annexin V-FITC/PI to detect apoptosis. Results showed 62.44% total apoptosis, close to that of cisplatin (71.28%) and significantly higher than the negative control (8.35%). These findings indicate strong pro-apoptotic potential of the fraction as a natural anticancer agent. Further research is recommended to identify the active compounds, confirm the molecular apoptosis pathway, and conduct in vivo tests for phytopharmaceutical development.